Cloning and expression of the exfoliative toxin B gene from Staphylococcus aureus. - Jackson, M P (1986)
Exfoliative toxin type B is produced by bacteriophage group II strains of Staphylococcus aureus and is a causative agent of staphylococcal scalded-skin syndrome. In addition to exfoliative toxin B, most isolates also produce a bacteriocin and are immune to the action of the bacteriocin. These phenotypes, as well as resistance to cadmium, were lost after elimination of a 37.5-kilobase plasmid, pRW001, from S. aureus UT0007. Transduction and transformation showed that pRW001 carries the structural genes for four phenotypic characteristics of S. aureus UT0007: (i) exfoliative toxin B production, (ii) bacteriocin production, (iii) bacteriocin immunity, and (iv) resistance to Cd(NO3)2. The exfoliative toxin B structural gene (etb), which is located on a 1.7-kilobase HindIII fragment of pRW001, was cloned in the plasmid pDH5060 and transformed into phage group III S. aureus RN4220. Transformant clones produced extracellular exfoliative toxin B that was biologically active in the neonatal mouse assay. In the Escherichia coli genetic background, the exfoliative toxin B gene was expressed only after being cloned into the positive selection-expression vector pSCC31. The structural gene for cadmium resistance was also isolated on an HindIII fragment of pRW001 cloned in pDH5060. The loci for the exfoliative toxin B gene and the cadmium resistance gene(s) were identified on a restriction map of plasmid pRW001.